Imprinting the economy: The structural power of venture capital - Franziska Cooiman (Environment and Planning A: Economy and Space, 2022)
This article analytically links asset management and the digital economy by analyzing the structural power of venture capital (VC) investors. Therefore, I propose the notion of imprinting, which describes how financial actors, enabled by their structural position, shape businesses according to their specific logic. Concretely, I argue that VCs' logic is one of assetization, whereby VCs turn startups into assets for themselves and their capital providers. To do so, VCs seek hypergrowth, selecting only companies with the potential to grow fast and large and decouple financial value from business fundamentals. Instead of the threat of exit, VCs establish direct and indirect channels of control: legally, via preferred shareholder rights, board seats, and payout conditionality; and as participatory capital, offering operational advice and access to their network. The article contributes to a nuanced understanding of financial sector power in contemporary capitalism.
Keywords: 330; structural power; venture capital; assetization; asset manager capitalism